THE REPLICATION CRISIS IN MARKETING: A FIELD-SPECIFIC DIAGNOSIS AND PRESCRIPTIONS FOR IMPROVING METHODOLOGICAL RIGOR - Indra Hidayat; Lukmanul Hakim; Dahrul Aman Harahap (RADJA PUBLIKA, 2026)
This study examines the replication crisis in marketing by providing a field-specific diagnosis and proposing methodological improvements to enhance research rigor. The replication crisis, characterized by the inability to reproduce empirical findings, has raised concerns about the credibility and reliability of marketing research. This article identifies key contributing factors, including questionable research practices such as p-hacking and selective reporting, lack of transparency in data and methods, publication bias favoring statistically significant results, and institutional pressures driven by the “publish or perish” culture. Using a qualitative literature review approach, this study synthesizes insights from prior research to explore the structural and methodological roots of the problem. The findings reveal that the replication crisis in marketing is not caused by a single factor but by an interconnected system of methodological weaknesses and institutional incentives. These issues undermine both the theoretical development of marketing and its practical applications in business decision-making. To address these challenges, the study proposes several key recommendations, including the adoption of open science practices, increased support for replication studies, improvements in research design and statistical analysis, and enhanced education on research ethics and methodology. By implementing these strategies, the marketing discipline can strengthen its scientific foundation, improve the reproducibility of findings, and restore trust in academic research.